Exploiting Microbial Diversity in Cocoa Ecosystems in Ghana to Control Phytophthora Pod Rot Disease - Akrofi, Andrews Y. (Global Journal of Food and Agribusiness Management, 2023)
Black pod disease, caused by different Phytophthora species, is a major yield-limiting factor in cocoa production. Currently, there is no acceptable genetic resistance to Phytophthora in cocoa varieties and pesticides used are not always effective, bring serious risks to human health and environment, and lead to resistance in pathogen populations. Recent studies in Ghana and the Netherlands on biological control of Phytophthora diseases have led to the isolation of several antagonistic bacteria that significantly limit the growth and proliferation of different Phytophthora species. Among the antagonistic bacteria, biosurfactant-producing Pseudomonas fluorescens isolates gave promising results in eliminating zoospore populations and controlling late blight disease of tomato caused by Phytophthora infestans. The objective of this study was to further develop these findings into effective control measures to manage black pod disease of cacao. This paper reports on the distribution and diversity of Pseudomonas and Phytophthora species associated with cocoa in Ghana and also describes preliminary results on the biocontrol activities of selected Pseudomonas strains against Phytophthora palmivora and Phytophthora megakarya.